A Proof of Komlós Theorem for Super-Reflexive Valued Random Variables - Abdessamad Dehaj; Mohamed Guessous (Axioms, 2020)
We give a geometrical proof of Komlós’ theorem for sequences of random variables with values in super-reflexive Banach space. Our approach is inspired by the elementary proof given by Guessous in 1996 for the Hilbert case and uses some geometric properties of smooth spaces.